2017
DOI: 10.18203/2394-6040.ijcmph20173314
|View full text |Cite
|
Sign up to set email alerts
|

Students’ sexual exposure in tertiary institutions: a case study of some universities in Abia state of Nigeria

Abstract: Background: Studies have shown that new entrants in institutions of higher learning are at risk of sexual exploits by older students. Drama has been identified as an intervention strategy capable of internalizing both the emotional and cognitive dimensions of sexual problems for positive changes. This study used drama to create awareness on likely common sexual exploits in institutions of higher learning. Methods: Study used first year students in three universities, federal, state and private. It was assumed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(27 reference statements)
1
1
0
Order By: Relevance
“…The results of the study reflect the suggestions of [27,29] that types of social exposure are primary determinants of youth sexual behaviours. Findings are also in support of the literature on ~ 20 ~ the intersectionality argument by [14,16,24] that sexual behaviours are shaped and determined by societal conditions and not necessarily by individual characteristics. Study provides further evidence that in order to promote protective sexual behaviours among students in higher institutions, social and gender-specific tactics should be adopted in the prevention of HIV and other STIs.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results of the study reflect the suggestions of [27,29] that types of social exposure are primary determinants of youth sexual behaviours. Findings are also in support of the literature on ~ 20 ~ the intersectionality argument by [14,16,24] that sexual behaviours are shaped and determined by societal conditions and not necessarily by individual characteristics. Study provides further evidence that in order to promote protective sexual behaviours among students in higher institutions, social and gender-specific tactics should be adopted in the prevention of HIV and other STIs.…”
Section: Discussionsupporting
confidence: 84%
“…This practice has been a source of concern in the prevention of HIV and other sexually transmitted infections [11][12][13] . Researchers have found that females, agreeing to have sex without condom was a necessary condition to avoid conflicts and assaults from male sex partners as well as to receive material goods and/or financial assistances [14][15][16][17] . Many researchers are of the opinion that condom use alone is not a sufficient HIV risk-reduction strategy because of the limitations of condoms [18,19] .…”
Section: Introductionmentioning
confidence: 99%